ANALISIS PEMAHAMAN AKUNTANSI KOPERASI PADA KOPERASI PETANI SAWIT SUMBER REZEKI DESA KEPENUHAN RAYA - Arma Yuliza (Jurnal Ilmiah Cano Ekonomos, 2015)
This study aims to determine the extent to which understanding of the cooperative smallholders source of sustenance village highway districts fullness fullness of accounting cooperative. Collecting data in this study using interviews and analyzed descriptively. Results from this study is that the oil bonanza farmers’ cooperative village fullness fullness highway districts that do not understand the accounting cooperative accounting has not been applied in preparing the financial statements cooperatives.